Lithium ion battery cell and preparation method thereof
By using reasonable positive electrode material ratio and electrolyte composition design in lithium-ion batteries, combined with high-capacity artificial graphite and ceramic separator, the existing lithium-ion batteries cannot meet pressure relief safety, rate discharge and The cycle life requirements are problematic, which achieves high energy density and stability, and is suitable for the application of electronic cigarette batteries.
Patent Information
- Application Number
- CN202411439184.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-31
AI Technical Summary
Existing lithium-ion batteries cannot meet the requirements of pressure relief safety test, 10C rate discharge capacity retention rate and cycle life in electronic cigarette applications, and the energy density is insufficient, which cannot meet the high volume energy density, high output power and high safety. At the same time, both.
The core, electrolyte and packaging material are wound from a positive electrode sheet, an anode sheet and a diaphragm. The electrolyte components include 10-15% lithium salt, 70-80% solvent system and 10-15% additives, and the solvent system is carbonic acid. Vinyl ester, dimethyl carbonate and propylene carbonate, additives are vinyl carbonate and toluene, the positive electrode materials are lithium cobalt oxide, ternary material and lithium manganate, and the negative electrode materials are high capacity and high compact secondary particles artificial graphite , with ceramic-coated separators, the stability and energy density of the battery are improved through reasonable raw material ratio and electrolyte design.
It realizes the high cycle life, stability and energy density of the battery, meets the requirements of pressure relief safety test and rate discharge test, and takes into account the energy density of the battery cell to ensure that the battery capacity retention rate is ≥300Wh/L under the 4.20V system, suitable for Large-scale production.
Smart Images

Figure CN119230962A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium-ion battery and a preparation method thereof. Background Art
[0002] At present, the batteries of electronic cigarettes are mainly soft-pack lithium-ion batteries. Such products require batteries to meet the performance of high volume energy density, high output power, low self-consumption and high safety. However, the soft-pack lithium-ion batteries currently used in electronic cigarettes cannot pass the pressure relief safety test 100%; even if they can pass the pressure relief safety test 100% through special processing, their 10C rate discharge capacity retention rate is about 30%, or even cannot discharge electricity. In addition, the cycle life is ≤100 weeks; another way is that the positive electrode material is selected to be lithium iron phosphate or lithium manganese oxide that can still exist stably under high voltage, but their pure energy density is low (energy density ranking: lithium cobalt oxide> ternary> lithium manganese oxide> lithium iron phosphate), which does not meet the use requirements. The above three methods cannot simultaneously meet the requirements of 100% passing the pressure relief safety test, 10C rate discharge capacity retention rate ≥ 85% and cycle life ≥ 300 weeks (300-week capacity retention rate ≥ 80%) while taking into account a certain energy density requirement. Therefore, it is necessary to design a lithium-ion battery cell that simultaneously meets the pressure relief safety test, rate discharge test, and cycle life test, while taking into account the energy density of the battery cell (4.20V system ≥ 300Wh / L). Summary of the invention
[0003] In order to solve the above technical problems, the present application provides a lithium-ion battery cell, including a core wound by a positive electrode sheet, a negative electrode sheet and a separator, an electrolyte and a packaging material, wherein the electrolyte components include 10-15% lithium salt, 70%-80% solvent system and 10-15% additives, the components of the solvent system include ethylene carbonate, dimethyl carbonate and propylene carbonate, and the components of the additive include vinylene carbonate and toluene.
[0004] Preferably, the mass ratio of ethylene carbonate, dimethyl carbonate and propylene carbonate is (4-5):(2-3):(2-3).
[0005] Preferably, the mass ratio of vinylene carbonate to toluene is (1-2):(8-9).
[0006] Preferably, the lithium salt concentration is 1.25 mol / L, the mass percentage of the lithium salt is 15%, the mass percentage of the solvent system is 74%, and the mass percentage of the additive is 11%.
[0007] Preferably, the diaphragm is a ceramic diaphragm coated with Al2O3 on one side, and the total thickness after coating is 12-20um.
[0008] Preferably, a preparation method for preparing the above-mentioned lithium-ion battery cell comprises the following steps:
[0009] S1, preparation of positive electrode sheet: lithium cobalt oxide, ternary material, and lithium manganese oxide are added into a stirring tank in a ratio of (1-2): (5-7): (2-3), and a conductive agent, a binder, and a solvent are added at the same time, and stirred thoroughly to obtain a uniformly dispersed positive electrode material, and the positive electrode material is uniformly coated on a substrate, and prepared into a slurry by a high-speed dispersing device, and after coating, roller compaction, and slitting, a positive electrode sheet of corresponding length is prepared, and an aluminum-to-nickel electrode ear is welded on the positive electrode sheet;
[0010] S2, preparation of negative electrode sheet: evenly coating the negative electrode material on the substrate, preparing it into slurry through high-speed dispersing equipment, coating, roller compacting, and slitting to make negative electrode sheets of corresponding length, and welding copper-plated nickel tabs on the negative electrode sheets, wherein the negative electrode material component is artificial graphite;
[0011] S3, the positive electrode sheet, the negative electrode sheet and the separator are wound by a winding machine to obtain a core, and then the core is pressed, packaged, baked, injected, aged, formed, sealed, divided and packaged in sequence to obtain a square soft-pack lithium-ion battery cell with a capacity of 400mAh.
[0012] Preferably, in step S1, 4.40V or 4.45V lithium cobalt oxide, 4.35V single crystal ternary, and 4.20V lithium manganese oxide are added into a stirring tank in different proportions.
[0013] Preferably, the negative electrode material on the negative electrode sheet has a gram capacity of ≥350 mAh / g, a particle size D50 of 10-15, and a compaction density of 1.65-1.70 g / cm 3 .
[0014] Preferably, the positive electrode material is coated on aluminum foil, and the negative electrode material is coated on copper foil, the copper foil is 6-10 um, and the aluminum foil is 10-16 um.
[0015] Preferably, the width of the positive electrode tab and the negative electrode tab is 2-8 mm.
[0016] As can be seen from the above, the following beneficial effects can be obtained by applying the present application: by designing the appropriate raw material ratio and mixing and doping the positive electrode material and the electrolyte to improve the stability of the positive electrode under overcharge conditions, while taking into account the energy density and improving the cycle life of the battery. The negative electrode adopts high-capacity and high-density secondary particle artificial graphite, and is matched with an electrolyte containing toluene anti-overcharge additives, plus a ceramic-coated diaphragm, which improves the overall stability and overcharge resistance of the battery cell, meets the pressure relief safety test while taking into account the energy density of the battery cell (4.20V system ≥300Wh / L), and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the drawings required for use in the description of the embodiments of the present application or the prior art are briefly introduced below. Obviously, the drawings described below are only part of the embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor.
[0018] Figure 1 This is a flow chart of the method for preparing a lithium-ion battery cell according to an embodiment of the present application;
[0019] Figure 2 This is a 10C rate discharge test curve diagram of the embodiment of the present application;
[0020] Figure 3 This is a test curve diagram of the 1C charging and 10C rate discharge cycle of the embodiment of the present application. DETAILED DESCRIPTION
[0021] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0022] Example 1
[0023] In order to solve the above technical problems, the present embodiment provides a lithium-ion battery cell, including a core wound by a positive electrode sheet, a negative electrode sheet and a separator, an electrolyte and a packaging material, the electrolyte components include 10-15% lithium salt, 70%-80% solvent system and 10-15% additives, the components of the solvent system include ethylene carbonate, dimethyl carbonate and propylene carbonate, and the components of the additive include vinylene carbonate and toluene.
[0024] Specifically, the mass ratio of ethylene carbonate, dimethyl carbonate and propylene carbonate in the solvent system is (4-5):(2-3):(2-3). Preferably, the mass ratio of ethylene carbonate, dimethyl carbonate and propylene carbonate is 5:2.5:2.5, and the mass ratio of vinylene carbonate and toluene in the additive is (1-2):(8-9), preferably, the mass ratio of vinylene carbonate and toluene is 2:8, wherein the addition of toluene can achieve the effect of preventing overcharging.
[0025] Furthermore, the concentration of the lithium salt is 1.25 mol / L, the mass percentage of the lithium salt is 15%, the mass percentage of the solvent system is 74%, and the mass percentage of the additive is 11%.
[0026] Furthermore, the diaphragm is a ceramic diaphragm coated with Al2O3 on one side, and the total thickness after coating is 12-20um, preferably 16um.
[0027] A preparation method for preparing the above-mentioned lithium ion battery cell, such as Figure 1 As shown, the following steps are included:
[0028] S1, preparation of positive electrode sheet: lithium cobalt oxide, ternary material, and lithium manganese oxide are added into a stirring tank in a ratio of (1-2): (5-7): (2-3), and a conductive agent, a binder, and a solvent are added at the same time, and stirred thoroughly to obtain a uniformly dispersed positive electrode material, and the positive electrode material is uniformly coated on a substrate, and prepared into a slurry by a high-speed dispersing device, and after coating, roller compaction, and slitting, a positive electrode sheet of corresponding length is prepared, and an aluminum-to-nickel electrode ear is welded on the positive electrode sheet;
[0029] In step S1, 4.40V or 4.45V lithium cobalt oxide, 4.35V single crystal ternary, and 4.20V lithium manganese oxide are added to a stirring tank in different proportions, and a conductive agent, a binder, and a solvent are added. The positive electrode material is fully stirred to obtain a uniformly dispersed positive electrode material, and the positive electrode material is evenly coated on the substrate. Among them, the positive electrode material is evenly coated on the aluminum foil, the thickness of the aluminum foil is 10-16um, and the preferred thickness of the aluminum foil is 12um. The aluminum-to-nickel tab is welded on the positive electrode sheet, and the width of the positive tab is 2mm. Preferably, 4.40V lithium cobalt oxide, 4.35V single crystal ternary, and 4.20V lithium manganese oxide are added to the stirring tank in a ratio of 1:7:2.
[0030] S2, preparation of negative electrode sheet: the negative electrode material is evenly coated on the substrate, and prepared into slurry through high-speed dispersing equipment. After coating, roller compaction, and slitting, the negative electrode sheet of corresponding length is made, and the copper-plated nickel pole ear is welded on the negative electrode sheet. Among them, the negative electrode material composition is high-capacity and high-density secondary particle artificial graphite. At the same time, it is matched with an electrolyte containing toluene anti-overcharge additives and a ceramic-coated diaphragm to improve the overall stability and overcharge resistance of the battery cell, meet the pressure relief safety test while taking into account the energy density of the battery cell, and can be mass-produced.
[0031] Specifically, artificial graphite, conductive agent, thickener and binder are mixed in a mass ratio of 95.5:1:1.3:2.2, and prepared into slurry by high-speed dispersing equipment. After coating, roller compaction and slitting, negative electrode sheets of corresponding length are made, and copper-plated nickel tabs are welded on the negative electrode sheets, and the width of the negative electrode tabs is 2mm. Among them, the gram capacity of the negative electrode material on the negative electrode sheet is ≥350mAh / g, the particle size D50 is 10-15, and the compaction density is 1.65-1.70g / cm 3 The negative electrode material is coated on a copper foil, and the thickness of the copper foil is 6-10 um, preferably 6 um.
[0032] S3, the positive electrode sheet, the negative electrode sheet and the separator are wound by a winding machine to obtain a core, and then the core is pressed, packaged, baked, injected, aged, formed, sealed, divided and packaged in sequence to obtain a square soft-pack lithium-ion battery cell with a system capacity of 400 mAh and a 4.20 V system.
[0033] Example 2
[0034] The present embodiment provides a lithium-ion battery cell, including a core wound by a positive electrode sheet, a negative electrode sheet and a separator, an electrolyte and a packaging material, wherein the electrolyte composition includes 10-15% lithium salt, 70%-80% solvent system and 10-15% additives, the components of the solvent system include ethylene carbonate, dimethyl carbonate and propylene carbonate, and the components of the additive include vinylene carbonate and toluene.
[0035] The positive electrode material preparation process of the positive electrode sheet is as follows: 4.40V lithium cobalt oxide, 4.35V single crystal ternary material, and 4.20V lithium manganate are added to a stirring tank in a ratio of 3:5:2, and then a conductive agent, a binder, and a solvent are added, and the mixture is stirred thoroughly to obtain a uniformly dispersed positive electrode material. Different from Example 1, Example 2 reduces the proportion of single crystal ternary material used, increases the proportion of 4.40V lithium cobalt oxide, and the other preparation steps are the same as Example 1, to obtain a 4.20V square soft-pack lithium-ion battery cell with a system capacity of 400mAh.
[0036] Example 3
[0037] The present embodiment provides a lithium-ion battery cell, including a core wound by a positive electrode sheet, a negative electrode sheet and a separator, an electrolyte and a packaging material, wherein the electrolyte composition includes 10-15% lithium salt, 70%-80% solvent system and 10-15% additives, the components of the solvent system include ethylene carbonate, dimethyl carbonate and propylene carbonate, and the components of the additive include vinylene carbonate and toluene.
[0038] The additive solvent of this embodiment 3 includes vinylene carbonate and toluene, wherein the mass ratio of vinylene carbonate to toluene is 5:5. Different from embodiment 1, the proportion of vinylene carbonate and toluene used in this embodiment is different, and the proportion of toluene used is reduced. The other preparation steps are the same as those in embodiment 1, and a square soft-pack lithium-ion battery cell with a system capacity of 400 mAh and a 4.20 V system is obtained.
[0039] Comparative Example
[0040] The present comparative example provides a lithium-ion battery cell, comprising a core wound up by a positive electrode sheet, a negative electrode sheet and a separator, an electrolyte and a packaging material, wherein the electrolyte components include 10-15% lithium salt, 70%-80% solvent system and 10-15% additives, the components of the solvent system include ethylene carbonate, dimethyl carbonate and propylene carbonate, and the components of the additive include vinylene carbonate and toluene.
[0041] The positive electrode material preparation process of the positive electrode sheet is as follows: 4.20V lithium cobalt oxide, 4.20V polycrystalline ternary material, and 4.20V lithium manganate are added to a stirring tank in a ratio of 1:7:2, and then a conductive agent, a binder, and a solvent are added, and the mixture is stirred thoroughly to obtain a uniformly dispersed positive electrode material. Different from Example 1, this comparative example uses 4.20V lithium cobalt oxide and 4.20V polycrystalline ternary material, and the other preparation steps are the same as those of Example 1, to obtain a 4.20V square soft-pack lithium-ion battery cell with a system capacity of 400mAh.
[0042] The soft-pack square lithium-ion batteries prepared in Example 1, Example 2, and Example 3 were subjected to pressure relief safety test, rate discharge test, and cycle life test; as a comparison battery, the positive electrode was made of conventional materials and subjected to a benchmark test.
[0043] Group By number Total number of tests Pass Rate Example 1 10 10 100% Example 2 4 10 40% Example 3 5 10 50% Comparative Example 2 10 20%
[0044] Table 1
[0045] Table 1 shows the pressure relief safety test results of each embodiment and comparative example. In the stability of the positive electrode, the stability is ranked as follows: lithium iron phosphate> lithium manganese oxide> ternary> lithium cobalt oxide, among which single crystal ternary materials are better than polycrystalline ternary materials. It can be seen from Table 1 above that in the positive electrode material, the use of a single crystal ternary material with a high voltage of 4.35V and increasing its use ratio in the positive electrode formula can significantly improve the stability of the positive electrode under overcharge conditions, improve the overall overcharge resistance of the battery cell, and ensure a 100% pass rate for the pressure relief safety test, while Example 2 and the comparative example reduce the use ratio of single crystal ternary and use polycrystalline ternary materials, which will greatly reduce the pass rate of the pressure relief safety test. In addition, reducing the use ratio of toluene in the components of the electrolyte additive solvent system will also reduce the pass rate of the pressure relief safety test. It can be seen that by designing a reasonable composition ratio of the positive electrode material and the use ratio of the electrolyte additive, the pass rate of the pressure relief safety test can be improved while taking into account the stability of the positive electrode and the energy density of the battery cell.
[0046] Group 1C Capacity 10C Capacity 10C capacity retention rate Example 1 414.80 392.39 94.60% Example 2 414.90 394.94 95.18% Example 3 409.80 394.12 96.17% Comparative Example 412.10 330.78 80.27%
[0047] Table 2
[0048] Table 2 above is a comparison table of rate discharge capability tests of various embodiments. Figure 2 Shown is the 10C rate discharge curve.
[0049] From Table 2 and Figure 2It can be seen that the rate discharge capabilities of Example 1 and Example 2 are basically the same, and Example 3 is slightly better than Example 1, and both are better than the comparative example. Therefore, in this electrochemical system, the positive electrode material made of high-voltage raw materials and the adjusted electrolyte can improve the rate discharge capability of the battery. In Example 3, the reduction in the proportion of the additive toluene can improve the rate discharge capability of the battery, but (as shown in Table 1) it will reduce the pass rate of the pressure relief test.
[0050] Group 10C initial capacity Cycle 300 cycles capacity Capacity retention rate Example 1 389.16 256.66 91.65% Example 2 424.15 338.56 72.82% Example 3 388.36 355.66 91.58% Comparative Example 422.23 334.25 79.16%
[0051] Table 3
[0052] Table 3 is a comparison table of cycle life tests of various embodiments. Figure 3 Shown is a 1C charge and 10C rate discharge cycle test curve.
[0053] As can be seen from the above figure and table, the cycle life performance of Example 1 and Example 3 is the best, and the capacity can still be maintained at more than 90% after 300 cycles, which is better than Example 2 and the comparative example. It can be seen that Examples 1 and 3 improve the stability of the positive electrode under overcharge conditions and improve the cycle life of the battery by mixing and doping different positive electrode materials and designing a suitable proportion of the electrolyte.
[0054] Based on the above test data, only Example 1 can simultaneously meet the three tests of pressure relief safety test, rate discharge test, and cycle life. By mixing and doping different positive electrode materials and designing the appropriate proportion of electrolyte to improve the stability of the positive electrode under overcharge conditions, while taking into account a certain energy density, the battery's rate performance, cycle life and the pass rate of the pressure relief safety test are improved. The negative electrode adopts high-capacity and high-density secondary granular artificial graphite, and is matched with an electrolyte containing an appropriate proportion of toluene anti-overcharge additives, plus a ceramic-coated diaphragm, which improves the overall stability and overcharge resistance of the battery cell, meets the pressure relief safety test while taking into account the energy density, and can be mass-produced.
[0055] The above-described implementation methods do not constitute a limitation on the protection scope of the technical solution. Any modification, equivalent replacement and improvement made within the spirit and principle of the above-described implementation methods shall be included in the protection scope of the technical solution.
Claims
1. A lithium-ion battery cell, characterized in that: It includes a winding core formed by winding a positive electrode sheet, a negative electrode sheet and a separator, an electrolyte and a packaging material. The electrolyte composition includes 10-15% lithium salt, 70%-80% solvent system and 10-15% additives. The components of the solvent system include ethylene carbonate, dimethyl carbonate and propylene carbonate. The components of the additive include vinylene carbonate and toluene.
2. The lithium-ion battery cell according to claim 1, characterized in that: The mass ratio of ethylene carbonate, dimethyl carbonate and propylene carbonate is (4-5):(2-3):(2-3).
3. The lithium-ion battery cell according to claim 1, characterized in that: The mass ratio of vinylene carbonate to toluene is (1-2):(8-9).
4. The lithium-ion battery cell according to claim 1, characterized in that: The lithium salt concentration is 1.25 mol / L, the mass percentage of the lithium salt is 15%, the mass percentage of the solvent system is 74%, and the mass percentage of the additive is 11%.
5. The lithium-ion battery cell according to claim 1, characterized in that: The diaphragm is a ceramic diaphragm coated with Al2O3 on one side, and the total thickness after coating is 12-20um.
6. A preparation method, characterized in that : for preparing the lithium ion battery cell according to any one of claims 1 to 5, The following steps are involved: S1, preparation of positive electrode sheet: lithium cobalt oxide, ternary material, and lithium manganese oxide are added into a stirring tank in a ratio of (1-2): (5-7): (2-3), and a conductive agent, a binder, and a solvent are added at the same time, and stirred thoroughly to obtain a uniformly dispersed positive electrode material, and the positive electrode material is uniformly coated on a substrate, and prepared into a slurry by a high-speed dispersing device, and after coating, roller compaction, and slitting, a positive electrode sheet of corresponding length is prepared, and an aluminum-to-nickel electrode ear is welded on the positive electrode sheet; S2, preparation of negative electrode sheet: evenly coating the negative electrode material on the substrate, preparing it into slurry through high-speed dispersing equipment, coating, roller compacting, and slitting to make negative electrode sheets of corresponding length, and welding copper-plated nickel tabs on the negative electrode sheets, wherein the negative electrode material component is artificial graphite; S3, the positive electrode sheet, the negative electrode sheet and the separator are wound by a winding machine to obtain a winding core, and then the winding core is successively subjected to the steps of core pressing, packaging, baking, liquid injection, aging, formation, secondary sealing, capacity division and packaging to obtain a square soft-pack lithium-ion battery cell.
7. The preparation method according to claim 6, characterized in that : In step S1, 4.40V or 4.45V lithium cobalt oxide, 4.35V single crystal ternary, and 4.20V lithium manganese oxide are added into a stirring tank in different proportions.
8. The preparation method according to claim 6, characterized in that : The negative electrode material on the negative electrode sheet has a gram capacity of ≥350 mAh / g, a particle size D50 of 10-15, and a compaction density of 1.65-1.70 g / cm 3 .
9. The preparation method according to claim 6, characterized in that :The positive electrode material is coated on aluminum foil, and the negative electrode material is coated on copper foil, the copper foil is 6-10um, and the aluminum foil is 10-16um.
10. The preparation method according to claim 6, characterized in that :The width of the positive electrode ear and the negative electrode ear is 2-8mm.
Citation Information
Patent Citations
Lithium-ion secondary battery
CN101288197A
High-capacity lithium-ion electrolyte, battery and preparation method of battery
CN101771167A
Rapidly discharged / charged high power lithium ion battery and manufacturing method thereof
CN108306013A
Anti-overcharge lithium ion electrolytic solution and lithium ion battery prepared by using anti-overcharge lithium ion electrolytic solution
CN108417891A
